1994
DOI: 10.1002/ajim.4700250213
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the extent of morbidity and mortality due to occupational diseases in Canada

Abstract: Occupational diseases are a significant and under-estimated cause of morbidity and mortality in Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
12

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 16 publications
(3 reference statements)
0
25
0
12
Order By: Relevance
“…If the unadjusted RR were available, then an unbiased estimate can be obtained by replacing P c in equation 2 by the expression P × RR / [P (RR -1) + 1] to obtain (20): A corresponding equation for case-referent sampling studies, analogous to equation 2, is as follows (23): AF = P c (OR a -1) / OR a , (equation 4) where OR a is the adjusted odds ratio. Equation 4 can be derived from equation 1 if it is assumed that the disease risk is low in the population from which the cases arose.…”
Section: Attributable Fraction Methodologymentioning
confidence: 99%
“…If the unadjusted RR were available, then an unbiased estimate can be obtained by replacing P c in equation 2 by the expression P × RR / [P (RR -1) + 1] to obtain (20): A corresponding equation for case-referent sampling studies, analogous to equation 2, is as follows (23): AF = P c (OR a -1) / OR a , (equation 4) where OR a is the adjusted odds ratio. Equation 4 can be derived from equation 1 if it is assumed that the disease risk is low in the population from which the cases arose.…”
Section: Attributable Fraction Methodologymentioning
confidence: 99%
“…Several investigators have recently attempted to estimate the magnitude and cost of occupationally-related mortality in the United States and elsewhere [Landrigan and Markowitz, 1989;Olsen and Kristensen, 1991;Kraut, 1994;Kerr et al, 1996;Leigh et al, 1997;Nurminen and Karjalainen, 2001]. For example, Leigh et al [1997] estimated 65,800 deaths each year can be attributed to occupational injury (6,500) or illness (60,300), with a total cost to society of over $23 billion.…”
Section: Introductionmentioning
confidence: 99%
“…Discussions continue regarding the actual extent of such WRMSD; i.e., the degree to which true incidence is different from the number of reported cases. Some studies suggest that WRMSD are in general under-reported [Fine et al, 1986;Gerr et al, 1991;Kraut, 1994;Maizlish et al, 1995;Oleinick et al, 1995;Rosenman et al, 2000]. The extent of potential under-reporting on the state or national level, if any, has been dif®cult to establish using traditional methods of looking at workers' compensation data, medical case series, or industry prevalence surveys.…”
Section: Introductionmentioning
confidence: 99%